A comprehensive evaluation of safety and awareness in eyebrow microblading: a cross-sectional study - Yahya Argobi; Norah Saad Jadaan; Waleed Obaid Alharbi; Sohaila Ahmed Asiri; Juri Ahmad Abdullah Alhatlani; Nujood Hassan Obaid; Seham Marei Ali Alqahtani (PAGEPress Publications, 2024)
The importance of eyebrows in facial aesthetics has long been recognized, and eyebrows restoration is carried out by carefully depositing pigments into the epidermis. This cosmetic procedure is known as microblading which is very popular because of the progress in social media platforms. This study was designed to determine the awareness of eyebrow microblading, complication and laser removal in general population of Saudi Arabia. This was a cross-sectional study conducted in four different regions in Saudi Arabia (Asir, Qasim, Jawf, and Eastern province), from June 2023 to December 2023. Only females were included, and an online questionnaire was distributed. A convenient non-probability sampling method was adopted to gather data from participants. Data analysis was performed using SPSS version 21. A total of 705 participants were included in the study, with the majority 281 (39.9%) falling into the age group >35 years, and the mean age was 29.1±11.9 years. The study revealed a moderate level of awareness (65%) among participants regarding eyebrow microblading. However, alarming gaps regarding hygiene practices in microblading setups still exist. Notably, facing complications during the surgery was identified as a statistically significant factor associated with a higher level of awareness (p=0.049). Of the participants, 17.4% had undergone eyebrow microblading, with friends being the source of advice for 39.5% of them. Laser removal was chosen by more than 60% of microblading recipients, with varying degrees of pleasure and satisfaction reported. Eyebrow microblading is a successful cosmetic procedure with aesthetic advantages. However, this study also emphasizes the necessity for extensive public education regarding microblading, including its associated risks, restrictions, and appropriate practices. To ensure safe and ethical practices, stringent laws and licensing for certified professionals are also deemed essential.